Effect of N, P, K and Cowdung on the Growth and Yield of Panchamukhi Kachu (Colocasia esculenta var. esculenta Schott.) (Journal of Agriculture & Rural Development, 2008)
A field experiment was carried out during two consecutive cropping seasons of 2001-02 and 2002-03 at the Agricultural Research Station, Raikhali, Rangamati, to optimize fertilizer need for desirable yield of Panchamukhi Kachu (Colocasia esculenta var. esculenta Schott.). Fourteen combinations of treatments consisting four levels of N (0, 50, 100 and 150 kg/ha), five levels of P2O5 (0, 25, 50, 75 and 100 kg/ha), four levels of K2O (0, 60, 120 and 180 kg/ha) and three levels of cowdung (0, 10, 20 and 30 t/ha) were tested. A positive impact of each nutrient and cowdung application was observed on vegetative growth and fresh yield of the crop. The highest yield (average of two years) of 35.20 t/ha (54% increase over control) was obtained with the application of 100 kg of N, 75kg P2O5, 180 kg, K2O and 10t cowdung/ha. From the economic point of view, the combination of 100 kg of N, 75kg P2O5, 180 kg K2O and 10 ton cowdung/ha was found to be the most suitable one which offered a gross return and gross margin of TK. 3.25 lakh/ha and Tk. 3.39 lakh/ha, respectively coupled with marginal rate of return as high as 3530.77%. Key words: Panchamukhi kachu, growth, yield.